Two Succenturiate Placentas in Dichorionic/Diamniotic (DC/DA) Twins – A Very Rare Case Presentation - B. Jeyamani; M Divya; S. Senthil Priya (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
This patient is a 45-year-old primigravida had conceived by fresh embryo transfer. ultrasound sonograph (USG) showed a dichorionic/diamniotic (DC/DA) type of twin. Serial ultrasounds showed normal growth and amniotic fluid levels for both twins. Cesarean section was done at 35 weeks. Both infants were admitted in the neonatal intensive care unit (NICU). The uniqueness of this case is the placenta, identified as dichorionic with two separate succenturiate lobes connected to the main placenta through communicating vessels. This exceptional case of placental variation, emphasises the importance of vigilant antenatal USG monitoring.